Pendidikan Karakter Religius Melalui Budaya Literasi Al-Qur’an Di Madrasah Aliyah Swasta Amaliyah Sunggal - Ismaraidha, Ismaraidha; Harahap, Muhammad Yunan; Hannum, Latifah (Jurnal Keislaman, 2024)
This study explores the implementation of religious character education through the culture of Quran literacy in Amaliyah Sunggal Private Islamic Senior High School. The main objective of this study is to identify and analyze how the culture of Quran literacy contributes to the formation of students' religious character and its impact on their learning and daily lives. The research method used is qualitative descriptive, involving observation, interviews, and documentation studies. Data analysis begins with data reduction, data presentation and drawing conclusions. Then to ensure the validity of the data, this study uses triangulation in order to increase the accuracy and credibility of the findings. The results of the study indicate that the implementation of the culture of Quran literacy has a positive impact on the development of students' religious character, increasing discipline, understanding of Islamic values, social sensitivity, and strengthening religious identity. However, this study also identified obstacles such as lack of student interest, limited teacher resources, dense curriculum, and negative influences of the social and technological environment. Strategies involving improving teacher competence, effective time management, and support from parents and the community are needed to overcome these obstacles.